Biosilicate® Glass-Ceramic Foams From Refined Alkali Activation and Gel Casting - Bernardo, Enrico; Elsayed, Hamada; Romero, Acacio Rincon; Crovace, Murilo C.; Zanotto, Edgar D.; Fey, Tobias (Frontiers in Materials, 2021)
Biosilicate® glass-ceramics are among the most valid alternatives to 45S5 Bioglass. They combine a similar bioactivity and bioresorbability as the 45S5 with superior mechanical strength, owing to the crystallization of a Na-Ca silicate phase. This crystallization may be experienced upon viscous flow sintering of fine glass powders, thus configuring a sinter-crystallization process. As crystallization is seldom complete, sintering can also be applied to semi-crystalline powders. The sintering/crystallization combination may be exploited for shaping highly porous bodies, to be used as scaffolds for bone tissue engineering, in the form of foams. The present paper aims at exploring a gel casting process, based on the room temperature foaming of powders suspended in a 'weakly alkaline’ (1M NaOH) aqueous solution, followed by sintering at 1000 °C. The gelation of suspensions is attributed to the formation of hydrated compounds, later decomposed upon firing. Amorphous powders provided more intense gelation than semi-crystalline ones, promoted a more homogeneous foaming and stimulated a substantial crystallization upon firing. The homogeneity of foamed samples was assessed using micro-tomography and was further improved by casting foamed suspensions ('foam casting') before setting.